El gran templo que nunca se llegó a construir. La catedral colonial de Cuenca (Ecuador) - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1993)
In this study we consider the problems posed by the building of the cathedral at Cuenca in Ecuador after the establishment of a bishopric in that city. This religious edifice was never built in the end because of the unachievable nature of the proposals and as a result of problems arising from the independence movement. Nevertheless, the documents generated allow us to get an idea of what the original mother church had been like, and what ambitions the bishops and local authorities had for the design of their new cathedral.